Role of HO/CO in the Control of Peripheral Circulation in Humans. (4th March 2012) - Sacerdoti, David; Mania, Despina; Pesce, Paola; Gaiani, Silvia; Gatta, Angelo; Bolognesi, Massimo
Abstract : Experimental studies show that the heme oxygenase/carbon monoxide system (HO/CO) plays an important role in the homeostasis of circulation and in the pathophysiology of hypertension. No data are available on its role in the control of peripheral circulation in humans. We evaluated the effects of inhibition of HO with stannous mesoporphyrin IX (SnMP) (200 μ M) locally administered by iontophoresis, on human skin blood flow, evaluated by laser-Doppler flowmetry, in the presence and absence of nitric oxide synthase (NOS) inhibition with L-NG-Nitroarginine methyl ester (L-NAME) (100 μ M). We also evaluated the effect of HO inhibition on vasodilatation induced by acetylcholine (ACh) and vasoconstriction caused by noradrenaline (NA). SnMP and L-NAME caused a similar 20–25% decrease in skin flow. After nitric oxide (NO) inhibition with L-NAME, HO inhibition with SnMP caused a further 20% decrease in skin perfusion. SnMP decreased vasodilatation induced by ACh by about 70%, while it did not affect vasoconstriction to NA. In conclusion, HO/CO participates in the control of peripheral circulation, independently from NO, and is involved in vasodilatation to ACh.